Presence of the Weakly Pathogenic Fusarium poae in the Fusarium Head Blight Disease Complex Hampers Biocontrol and Chemical Control of the Virulent Fusarium graminearum Pathogen - Tan, Jiang; De Zutter, Noémie; De Saeger, Sarah; De Boevre, Marthe; Tran, Trang Minh; van der Lee, Theo; Waalwijk, Cees; Willems, Anne; Vandamme, Peter; Ameye, Maarten; Audenaert, Kris (Frontiers in Plant Science, 2021)
Fusarium head blight (FHB) in wheat (Triticum aestivum L.) is caused by a consortium of mutually interacting Fusarium species. In the field, the weakly pathogenic F. poae often thrives on the infection sites of the virulent F. graminearum. In this ecological context, we investigated the efficacy of chemical and biocontrol agents against F. graminearum in wheat ears. For this purpose, one fungicide comprising prothioconazole + spiroxamine and two bacterial biocontrol strains, Streptomyces rimosus LMG 19352 and Rhodococcus sp. R-43120 were tested for their efficacy to reduce FHB symptoms and mycotoxin (deoxynivalenol, DON) production by F. graminearum in presence or absence of F. poae. Results showed that the fungicide and both actinobacterial strains reduced FHB symptoms and concomitant DON levels in wheat ears inoculated with F. graminearum. Where Streptomyces rimosus appeared to have direct antagonistic effects, Rhodococcus and the fungicide mediated suppression of F. graminearum was linked to the archetypal salicylic acid and jasmonic acid defense pathways that involve the activation of LOX1, LOX2 and ICS. Remarkably, this chemical- and biocontrol efficacy was significantly reduced when F. poae was co-inoculated with F. graminearum. This reduced efficacy was linked to a suppression of the plant’s intrinsic defense system and increased levels of DON. In conclusion, our study shows that control strategies against the virulent F. graminearum in the disease complex causing FHB are hampered by the presence of the weakly pathogenic F. poae. This study provides generic insights in the complexity of control strategies against plant diseases caused by multiple pathogens.